Improving Patient Involvement in the Lifecycle of Medicines: Insights From the EUPATI BE Survey - Grine, Lynda; Janssens, Rosanne; van Overbeeke, Eline; Derijcke, Danielle; Silva, Mitchell; Delys, Belinda; Dusart, Isabelle; Aertsen, Veerle; Mertens de Wilmars, Magali; Robaczewska, Joanna; Stevens, Hilde (Frontiers in Medicine, 2020)
EUPATI Belgium (EUPATI.be) is an informal gathering of local partners who are interested in improving patient involvement in healthcare innovation and medicines research and development. EUPATI.be brings together various stakeholders from different areas related to healthcare including patients, academia and industry. In doing so, we create an innovative collaborative approach where actors from different backgrounds work towards improving patient involvement in medical research, and putting the patient at the center of the Belgian healthcare system. Previously, we performed in-depth interviews with a small group of stakeholders on patient involvement. Here, we elaborate on our previous findings by using a nation-wide survey to inquire into Belgian stakeholders’ perception on patient involvement. To this end, an electronic survey was available in French, Dutch and English, and accessible for 11 months. Twelve questions were asked, including 11 multiple choice questions and 1 open question. The latter was thematically analyzed according to the framework method. A total of 117 responses were registered and descriptive statistics were performed. The majority of respondents could be categorized into patient, academia and industry, whereas policy makers, payers and healthcare professionals were underrepresented. We identified several barriers that hamper patient involvement, which were sometimes more reported by specific stakeholder groups. Next, we found that various stakeholders still consider patient involvement as a passive role, i.e. medical subject in a clinical trial. Respondents also reported that the role of the various stakeholders needed more clarification; this was also confirmed by the level of trust amongst the various stakeholders. Existing and the wish for more collaboration with the various stakeholders was reported by almost all respondents. Based on this survey, we can define the potential of involving patients in the medical research and development in the Belgian landscape. Our results will help to understand and tackle the various barriers that currently hamper patient involvement, whilst highlighting the need for a collaborative landscape from the multi-stakeholder perspective.